The Impact of Regional Fund on Unemployment - Holik, Abdul (Universitas Negeri Semarang, 2020)
This research attempts to find the impact of the government budget on unemployment in West Java. It is conducted from 2006 until 2015. The data used here is secondary data from Centre of Indonesian Statistics (BPS). It consists of a general allocation fund (DAU), specific allocation fund (DAK), profit-share of tax and non-tax fund as independent variables. Meanwhile, set unemployment as the dependent variable. The method of analysis is Panel Regression with Fixed Effect. Because we firstly face awkward result when analyzing model by including all independent variables, then we try to estimate every single independent variable on the dependent variable. Therefore we have four models to dig the problem to its root. Based on the analysis result, it is founded that all independent variables have a negative and significant impact on the dependent variable. It signifies that unemployment can be on the wane due to various budget policies of a nation which directed to the regional development. The bigger the agenda development made, the bigger the decreasing unemployment rate because everybody can be absorbed into employment.